Classroom-Based Indicators of Assessment Coherence in Cross-Curricular Projects - Karkhaneh, Yasna (Assessment and Practice in Educational Sciences, 2024)
This study aimed to identify classroom-based indicators of assessment coherence in cross-curricular projects as perceived by teachers in Tehran, with a focus on practices that align learning goals, instructional activities, and assessment strategies. A qualitative research design was employed, involving semi-structured interviews with 26 teachers and curriculum specialists from primary and secondary schools in Tehran who had experience with cross-curricular project implementation. Data collection continued until theoretical saturation was achieved. Interviews were audio-recorded, transcribed verbatim, and analyzed thematically using NVivo software. The analysis followed an open coding process, with codes and themes refined through constant comparison and member checking to ensure rigor and trustworthiness. Three major themes emerged from the data: (1) Alignment of Learning Goals and Tasks, which included shared learning objectives, unified assessment criteria, integrated content, balanced subject representation, collaborative curriculum mapping, and reflective alignment reviews; (2) Collaborative Instructional Practices, encompassing co-teaching, regular planning meetings, professional development, structured communication, student involvement in planning, and conflict resolution strategies; and (3) Evidence and Use of Learning Outcomes, which comprised the use of multiple forms of evidence, continuous feedback mechanisms, systematic documentation, transparent reporting, and reflection on learning. Teachers highlighted the importance of joint planning, diversified assessment, and participatory approaches for maintaining coherence and student engagement in cross-curricular projects. The findings underscore the significance of structured teacher collaboration, diversified assessment evidence, and ongoing reflective practice in achieving assessment coherence within cross-curricular projects. Supporting these practices through school-level structures, targeted professional development, and inclusion of student voice is essential for advancing the quality and impact of integrated education. These results offer actionable recommendations for educators and policymakers aiming to foster coherent, equitable, and meaningful assessment in interdisciplinary learning environments.